Comparison of bullet stration pattern using ibis bullettrax-3d and aliconainfinite focus microscope - Anting, Maria Magdalina Dennis J (Universiti Sains Malaysia, 2016)
Firearm identification is a process to determine whether a bullet or cartridge was fired by a particular weapon based on individual characteristic. The unique patterns created on the surfaces of the bullet or cartridge carry an individual characteristic which is useful for firearm identification. Four different pistols of same model were used in this study and six bullets were obtained per pistol. The objective of this study is to exercise objective comparison of bullet striation patterns within the same model of semiautomated pistols, Walther P99 by automated comparison performed using Integrated Bullet Identification System (IBIS) BULLLETRAX-3D and Alicona-Infinite Focus Microscope. IBIS BULLETTRAX-3D gives 3D images of the bullet’s surfaces while Alicona-Infinite Focus Microscope also gives images and surface topography measurement for identification. Analysis using IBIS BULLETTRAX-3D showed striation images which required the final decision by the examiner for bullet identification. Meanwhile, Alicona-Infinite Focus Microscope also captured visual images of the bullet surface as well as surface topography profile with dataset for each sample. Pairwise comparison with Pearson Product Moment Correlation (PPMC) from summarised datasets showed positive correlation among the bullet fired from the gun (r = 0.99 and above). Both methods potentially may complement each other and will be beneficial for forensic firearm identification.